2022
DOI: 10.1371/journal.ppat.1010438
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii phosphatidylserine flippase complex ATP2B-CDC50.4 critically participates in microneme exocytosis

Abstract: Regulated microneme secretion governs motility, host cell invasion and egress in the obligate intracellular apicomplexans. Intracellular calcium oscillations and phospholipid dynamics critically regulate microneme exocytosis. Despite its importance for the lytic cycle of these parasites, molecular mechanistic details about exocytosis are still missing. Some members of the P4-ATPases act as flippases, changing the phospholipid distribution by translocation from the outer to the inner leaflet of the membrane. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Our finding that NBD-PC uptake is unaffected in CDC50C null trophozoites suggests that either ATP2 transports another phospholipid or that lipid uptake in trophozoites occurs via (multiple) redundant pathways. During the preparation of this article, a recent study found that the T. gondii orthologue of CDC50C, CDC50.4, binds ATP2B, an essential P4-ATPase that transports PS ( 55 ). This CDC50.4-ATP2B complex is required for efficient microneme secretion in tachyzoites with no defect observed during parasite intracellular development ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that NBD-PC uptake is unaffected in CDC50C null trophozoites suggests that either ATP2 transports another phospholipid or that lipid uptake in trophozoites occurs via (multiple) redundant pathways. During the preparation of this article, a recent study found that the T. gondii orthologue of CDC50C, CDC50.4, binds ATP2B, an essential P4-ATPase that transports PS ( 55 ). This CDC50.4-ATP2B complex is required for efficient microneme secretion in tachyzoites with no defect observed during parasite intracellular development ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this article, a recent study found that the T. gondii orthologue of CDC50C, CDC50.4, binds ATP2B, an essential P4-ATPase that transports PS ( 55 ). This CDC50.4-ATP2B complex is required for efficient microneme secretion in tachyzoites with no defect observed during parasite intracellular development ( 55 ). It is plausible that the P. falciparum CDC50C-ATP2 complex may perform a similar role in egressed merozoites, but this could not be addressed in our study due to the block in intraerythrocytic development in CDC50C null parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, they identified Transporter Facilitator Protein 1 (TgTFP1) ( Hammoudi et al., 2018 ), an essential protein for parasite survival due to its crucial role in microneme biogenesis and maturation. In 2016, the identification of the protein acylated pleckstrin homology domain-containing protein (TgAPH) as a phosphatidic acid sensor anchored at the surface of the micronemes ( Bullen et al., 2016 ) prompted the lab to investigate the signaling cascade leading to microneme secretion and parasite egress ( Bullen et al., 2016 ; Jia et al., 2017 ; Darvill et al., 2018 ; Bisio et al., 2019 ; Bisio et al., 2022 ) and, with other labs, to draw the picture we know today ( Farrell et al., 2012 ; Brown and Sibley, 2018 ; Bisio and Soldati-Favre, 2019 ; Bullen et al., 2019 ; Yang et al., 2019 ).…”
Section: Understanding Toxoplasma At the Molecular...mentioning
confidence: 99%
“…Knockdown of TgP4-ATPase1-3 impairs parasite growth in human host cells 6 . Furthermore, TgP4-ATPase and its CDC50 chaperone (ATP2B-CDC50.4) act as a flippase and contribute to the enrichment of PtdSer in the inner leaflet of the parasite plasma membrane 7 . The asymmetric distribution of PtdSer in the cytoplasmic leaflet (PF) of the plasma membrane has been suggested to be important for microneme exocytosis.…”
Section: Introductionmentioning
confidence: 99%